PENGARUH MODEL DISCOVERY LEARNING TERHADAP PEMAHAMAN KONSEP MATEMATIS DALAM MENYELESAIKAN SOAL CERITA PESERTA DIDIK KELAS VIII SMP NEGERI 25 PADANG - Sifa, Friska Falah (Departemen Matematika, 2024)
A person can't build more talents on top of a solid grasp of mathematical ideas. Students can't hope to solve mathematics word problems or any other real-world difficulty without first mastering the underlying ideas. In reality, eighth graders at SMP Negeri 25 Padang continue to have below-average academic performance. To overcome this obstacle, we will utilize the Discovery Learning method. The Nonequivalent Posttest-Only Control Group Design is a quasi-experimental research strategy that was utilized in this study. The Simple Random Sampling method was employed to carry out the sampling. The final evaluation in the form of narrative-based problems is the research instrument utilized. The t-test data analysis yielded a p-value of 0.10, which is lower than the 0.05 criterion of significance. This proves that H0, the null hypothesis, is not true. Students that use the DL model outperform their peers who rely on traditional, hands-on methods of instructionKeywords– Understanding Mathematical Concepts, Discovery Learning, Story Problems